A qualitative analysis of social scientists' opinions on socioeconomic and demographic implications of the lockdown during COVID‐19 in India. Issue 3 (22nd October 2020) - Gupta, Priya; Sengupta, Angan
Abstract : The unpredictable dynamics of COVID‐19 and policies surrounding its management has triggered severe debates and discussions among every section of society. There have been similarities as well as differences in opinions regarding spread of the disease, the lockdown, its implementations and impacts. This qualitative study attempts to identify and understand the emerging pattern within the opinions of 16 social scientists from eminent institutes with rich socioeconomic and demographic research experience. Several key themes emerged from this study. While it is opined that the lockdown initially slowed down the spread of virus among Indian population, it continues to surge exponentially. Economy faced extreme hardship because of this extensive and abrupt national lockdown. State‐wise variation in the COVID‐19 scenario is noticed and the reason is attributed to the strictness of implementation of the lockdown by the respective state governments. However, a lockdown in phases is suggested that could have averted the economic crisis. Small businesses were the hardest hit. Migrant workers were not given deserved attention and support in terms of their travel to their natives, health or financial sustenance during the lockdown. The bailout has not been timely and enough thereby creating a group of new poor. From the opinions it emerges that the policy measures intended to revive back the micro, small and medium scale enterprises may not bring short‐term solution pertaining to the labor crisis. Relaxation of lockdown also calls for stringent awareness generation among general population about health and hygiene maintenance to avoid further spread of COVID‐19.